Marine Heatwaves in the Mediterranean Sea: A Literature Review - DARMARAKI, SOFIA; DENAXA, DIMITRA; THEODOROU, IASON; LIVANOU, ELENI; RIGATOU, DIONYSIA; RAITSOS E., DIONYSIOS; STAVRAKIDIS-ZACHOU, ORESTIS; DIMARCHOPOULOU, DONNA; BONINO, GIULIA; McADAM, RONAN; ORGANELLI, EMANUELE; PITSOUNI , ALEXIA; et al. (Mediterranean Marine Science, 2024)
Marine heatwaves (MHWs) are prolonged periods of exceptionally warm temperatures in the ocean, which have forced profound transformations in marine biodiversity and socio-economic systems globally over the last decades. The Mediterranean basin, a highly vulnerable area to climate change, has been particularly affected as a marginal sea, experiencing multifaceted changes due to these events. This literature review brings together a comprehensive list of interdisciplinary research on MHW evolution in the Mediterranean basin, from the past to the future, covering the most common driving mechanisms of MHWs, known feedbacks and impacts on various marine organisms and local economies. Aiming to enhance our understanding of Mediterranean MHWs across various dimensions, we further discuss ongoing challenges in their detection and characterization, highlighting the need to improve monitoring systems and forecasting capabilities using novel approaches in the basin and beyond.